Integrative Islamic Education Model Based on Gayo Cultural Wisdom - Dedi Wahyudi; Mahdi; Salami; Sri Handayana (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
Local Gayo culture in Bener Meriah plays a pivotal role in shaping religious values, providing a relevant foundation for the development of Islamic Education (PAI). Consequently, this study aims to formulate an integrative Islamic Education model based on Gayo cultural wisdom. To achieve this objective, a qualitative research design with an ethnographic approach was employed to explore and map the cultural values potential for integration into the PAI learning model. The findings indicate that Gayo cultural wisdom embodies profound religious values that serve as strategic guidelines for designing a contextual and adaptive PAI model. Thus, the integration of local cultural values not only enriches religious education content but also strengthens the social relevance and distinct characteristics of the pedagogical model. In conclusion, the integrative Islamic Education model based on Gayo cultural wisdom offers a contextual and strategic approach to advancing religious education rooted in cultural identity.